Examining English teacher professionalism through dialogic narrative inquiry: a case from Sabah, Malaysia - Loo, Daron Benjamin (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study reports the examination of the professionalism of a local English teacher in Sabah, Malaysia, through dialogic narrative inquiry. The purpose of this examination is to understand ways in which professionalism of a local English teacher in a setting where English is minimally spoken is enacted in light of different social entities and objects, as well as prescriptive expectations. Narratives from the teacher, Misha, concerning her teaching were collected over seven months. Subsequently, the narratives were restoried by the researcher and Misha over four months, resulting in narrative constellations which described variables that affected Misha professionally. The constellations are Misha’s self, her students, her colleagues and the English Teaching Assistant, as well as the prescribed materials and pedagogy. The findings support the notion that teacher professionalism is a dynamic and multi-faceted construct. Furthermore, the study provides an avenue for the legitimization of an English language teacher through thoughts and actions reflected through narratives.